Characterization of the whole plastid genome sequence of Abies chensiensis (Pinaceae), an endangered endemic conifer in China. Issue 2 (3rd July 2018) - Liu, Mi-Li; Bai, Ji-Qing; Dong, Wan-Lin; Wang, Ruo-Nan; Dong, Peng-Bin; Wang, Ning-; Liu, Hong-Yan; Fang, Min-Feng
Abstract: Abies chensiensis Van Tiegh. (Pinaceae) is a rare and endangered endemic conifer in China. In this study, using the Illumina sequencing platform, we firstly characterized its whole plastid genome sequence. Our study revealed that A. chensiensis have a typical plastid genome of 121, 498 bp in length, comprised of a large single copy region of 76, 484 bp, a small single copy region of 42, 654 bp and two inverted repeat regions of 1180 bp. A total of 113 genes, 74 protein-coding genes, 35 tRNA, and 4 rRNA genes were identified. The phylogenetic analysis indicated that A. chensiensis was placed as a sister to the congeneric A. sibirica .